Cachorro carinoso : un cantito de amor - Boynton, Sandra (Nueva York : Workman Publishing, 2019)
Los padres de Snuggle Puppy expresan amor por su cachorrito por medio de una cancion.
"Boynton clasico"
On board pages.
Translation of: Snuggle puppy!
In Spanish = En espanol.
Keywords: Parent and child -- Juvenile fiction; Dogs -- Juvenile fiction; Love -- Juvenile fiction; Puppies -- Juvenile fiction; Parent and child -- Fiction; Spanish language materials -- Juvenile fiction; Love -- Fiction; Dogs -- Fiction; Spanish language materials -- Fiction; Stories in rhyme; Board books; Padres e hijos -- Novela juvenil; Perros -- Novela juvenil; Fiction